Energy consumption of Twisted File instrument used with rotary or reciprocating adaptive motion - Özyürek, Taha; Keskin, Cangül; Demiryürek, Ebru Özsezer (European Journal of General Dentistry, 2016)
Objective: The aim of this study was to compare the energy consumption of Twisted File (TF) instrument used with rotary or adaptive motion (AM). Materials and Methods: Forty S-shaped Endo Training Blocks (Dentsply Maillefer) were used. Twenty were prepared using TF 25.06 in rotary motion (RM) group, and 20 were prepared using TF Adaptive SM2 in AM group. While engine-driven endodontic motors were connected to a digital wattmeter, the required torque for root canal instrumentation was analyzed by evaluating the electrical power consumption of the endodontic engine. Electric power consumption (mW/h), elapsed time (s), and a number of pecking motions required to reach the full working length (WL) were calculated. The data was statistically analyzed using Mann-Whitney U-test (P < 0.05). Results: Electrical power consumption during the preparation was significantly different between the groups; RM group exerted less electric power than reciprocating AM group did (P < 0.001). The required time to reach the full WL was not statistically significant between groups (P = 0.137). Conclusion: Within the limitation of this study, RM group exerted less electric power than reciprocating AM group did.
Keywords: Electric power consumption; nickel–titanium; nickel–titanium rotary preparation; Twisted File Adaptive